Myanmar : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes banking sector developments in Myanmar. It highlights that latent banking sector risks are surfacing, following a period of rapid credit growth and as banks adjust to updated financial regulations. Over time banks will need to enhance their credit risk management, and reduce the over-reliance on collateral values to safeguard lending. A banking system action plan has been developed, to enhance the banking system's resilience, as well as strengthen the supervisory and resolution framework. The ongoing overhaul of the prudential framework and financial sector reforms will strengthen the banking sector and its role in supporting the economy.